Ultrafast high-temperature sintering of silicon nitride: A comparison with the state-of-the-art techniques. Issue 13 (October 2021) - Luo, Rui-Xin; Kermani, Milad; Guo, Zhao-Liang; Dong, Jian; Hu, Chun-Feng; Zuo, Fei; Grasso, Salvatore; Jiang, Bei-Bei; Nie, Guang-Lin; Yan, Zheng-Qing; Wang, Qiang; Gan, Yan-Ling; et al.
Abstract: Ultrafast High-temperature Sintering (UHS) has been successfully applied to fabricate the silicon nitride (Si3 N4 ) bulks, as the first attempt of ultra-rapid consolidation of a non-oxide ceramics. At a heating rate of 875 °C/min, the bulk Si3 N4 ceramic with a relative density greater than 96 % and an α-β phase transformation degree above 80 % could be obtained within 300 s. The effects of ultrafast heating on the liquid phase sintering (LPS) were also comparatively studied. Results showed that, the ultrafast heating rate and high temperature under UHS might promote the LPS system evolving to a nonequilibrium state. By comparing with other pressureless sintering processes with much lower heating rates, UHS apart from reducing the processing time, and it is also an effective method to form a bimodal microstructure composed of interlocked rod-like β-Si3 N4 grains.